Lived experiences of persons on tuberculosis treatment in Nairobi County, Kenya: a mixed methods study - Joan Ondiro; Faith Onyangore; Reagan Onyango; Lenah Muema; Dickens S. Omondi Aduda (BMC Public Health)
Abstract Background Tuberculosis program effectiveness is majorly measured by disease severity and treatment response without integrating patient perspectives. Yet, it’s a critical dimension in clinical decision-making that enhances health worker-patient interactions and increases individuals’ sustained engagement with treatment, thereby benefiting the people affected and the wider public by mitigating the infection risk. This study assessed the lived experiences of persons affected by tuberculosis who were on treatment in Nairobi County, Kenya. Methods A cross-sectional study was conducted in May 2023 among 392 persons with drug-susceptible pulmonary tuberculosis in five facilities in Nairobi County. Participants were selected through simple random sampling and interviewed by semi-structured questionnaires and focused group discussions. Data on prevention and control strategies, facility preference, medication burden, interaction with healthcare workers, and the socio-economic effects of the disease were collected. Quantitative data was analyzed descriptively using frequencies, percentages, means, and standard deviations while qualitative data was transcribed, coded, and thematically analyzed. Results The sample consisted of 245 males and 147 females aged between 3 and 74 years. Despite the high rating of their interactions with the healthcare workers, the findings show insufficient knowledge of the prevention and control strategies of TB. Additionally, food insecurity resulting from an inability to afford recommended meals, medication burden such as high pill burden especially where there are coexisting medical conditions, undesirable taste and size of the TB tablets, adverse drug events, economic burden due to loss of income, and stigma from the family and community were reported to affect treatment outcomes. Conclusion Treatment outcomes are influenced by multi-level factors such as low knowledge of TB prevention and control strategies, stigma, food insecurity, medication burdens like pill number, size, taste, and adverse drug reactions, facility preference, and economic hardships including loss of income. Understanding the individual needs of persons with TB will help develop interventions that are specific to them for better treatment outcomes.